ASSESSMENT OF THE EFFECTIVENESS OF SELF-MANAGEMENT IN OUT PATIENT PATIENTS WITH TYPE 2 DIABETES MELLITUS - Bahriyeva, Nigora Naimovna; Mahmudova, Intizor Abdurauf qizi; Keldiyorova , Navbahor Nuriddin qizi; Nazarov , Qilichbek Ilxom o‘g‘li (Educational Research in Universal Sciences, 2024)
Diabetes mellitus, along with other socially significant non-communicable diseases, is one of the most pressing problems of society due to its widespread prevalence, the presence of serious complications, and significant social and economic losses1–3,3–7. The International Diabetes Association estimates that 415 million adults have diabetes in 2015. About 5 million people aged 20 to 79 have died due to diabetes. In Kazakhstan as of December 2014 244,541 patients with diabetes mellitus were registered, which corresponds to an incidence of 164.4 per 100 thousand population4,8–11. It is important to note that type 2 diabetes largely depends on the patient’s behavioral factors, which indicates the need to influence, first of all, changing habits, lifestyle and developing healthy behavioral attitudes. People with diabetes need to develop skills to manage their behavioral risk factors, use health services and medications effectively, and cope with the impact of the disease on their daily lives12–17.